2019
DOI: 10.1186/s41983-019-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic complaints profile in patients with type 2 diabetes: a matched case-control study

Abstract: Objective: To compare the prevalence of psychosomatic symptoms and their mean scores of profiles in diabetic patients and sample of sex-age-matched healthy controls. Methods: This case-control study was conducted on 87 patients with type 2 diabetes. The control group consisted of 259 age-and gender-matched healthy participants. Psychosomatic symptoms were assessed using a comprehensive 31-item questionnaire, and psychological problems were evaluated by 12-item General Health Questionnaire and Hospital Anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…We had expected that both mental and somatic stressors would be an obstacle for participants' activity levels during that day. Individuals with T2DM may experience a variety of mental and somatic stressors, such as sadness (Darwish et al, 2018) and pain (Heidari et al, 2019), and some of these have been associated with more sedentary behaviour and low levels of PA. For example, Chastin et al (2014) found that pain was one of the main drivers for being sedentary, albeit not in a sample of patients with T2DM. There are at least three explanations for the current results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We had expected that both mental and somatic stressors would be an obstacle for participants' activity levels during that day. Individuals with T2DM may experience a variety of mental and somatic stressors, such as sadness (Darwish et al, 2018) and pain (Heidari et al, 2019), and some of these have been associated with more sedentary behaviour and low levels of PA. For example, Chastin et al (2014) found that pain was one of the main drivers for being sedentary, albeit not in a sample of patients with T2DM. There are at least three explanations for the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Participants filled out the morning diary using their personal computer or tablet and could only access and complete the morning diary between 3 AM and 11 AM. The morning diary assessed mental and somatic stressors that are prevalent in individuals with T2DM (i.e., fatigue (Fritschi & Quinn, 2010;Heidari et al, 2019), stress (Hackett & Steptoe, 2017;Qiu et al, 2017), sadness (Ali et al, 2006;Darwish et al, 2018), pain (Heidari et al, 2019;Kirk et al, 2019), nausea/dizziness (Heidari et al, 2019) and numbness/tingling in the limbs (Aikens, 1998;Kästenbauer et al, 2004)). All mental and somatic stressors were assessed using single-item measures.…”
Section: Daily Mental and Somatic Stressorsmentioning
confidence: 99%
See 1 more Smart Citation